ANALYSIS OF THE EFFECTIVENESS OF INTEGRATING DIAGNOSTIC TOOLS AND CONTROL SYSTEMS INTO MANAGEMENT PROCESSES OF AGRICULTURAL ENTERPRISES: EXPERIENCE AND PROSPECTS - TKACHENKO, Vyacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the effectiveness of integrating diagnostic tools and controlling systems in the management processes of agricultural enterprises, which is a critical factor in increasing competitiveness in the contemporary market environment. The research analyzes current approaches to implementing control in the agricultural sector, with particular emphasis on the use of various diagnostic methods to assess enterprises’ financial condition, productivity, and risk. The study characterizes the advantages and disadvantages of existing controlling systems and examines their impact on management decision-making and long-term planning. Integration of controlling systems is examined through a detailed analysis of how these tools contribute to more accurate forecasting, efficient resource allocation, and improved financial performance. By analyzing case studies and empirical data from agricultural enterprises, the article offers a comprehensive review of the practical applications of these systems in real-world scenarios. The research emphasizes the critical role of controlling and identifying operational inefficiencies and optimizing management strategies to reduce costs and increase profitability. Moreover, the article presents practical recommendations for optimizing the integration processes of diagnostic tools and control systems. It underscores the importance of a tailored approach that considers the specific characteristics of agricultural enterprises. These recommendations are designed to assist managers in enhancing their management systems, leading to improved decision-making, increased operational efficiency, and enhanced overall performance. The results of this study are particularly pertinent to managers and decision-makers in the agricultural sector. They provide valuable insights for those seeking to enhance their management practices by adopting innovative approaches to control and diagnostics. The paper concludes that the successful integration of these systems can significantly contribute to the sustainable development of agricultural enterprises, enabling them to navigate the challenges of a dynamic and competitive market environment.